Sound sleep, sound mind : - Krakow, Barry (Wiley, 2007)
Sound Sleep, Sound Mind is the first book of its kind to focus on all the causes--mental, emotional, and physical--that contribute to insomnia and poor sleep. Based on cutting-edge knowledge and research, this book explains why sleep problems are almost always a mind and body issue. It then guides you through the seven steps of Sleep Dynamic Therapy to identify and treat the specific problems that are at the root of your sleeplessness. You'll discover that the Sleep Dynamic Therapy program not only improves your sleep quality, but also enhances many other aspects of your mental and physical well-being.